Co 2 Laser Treatment for Vaginal Intraepithelial Neoplasia, Assesment of Recurrence - Ángel García-Iglesias; Ángel García- Sánchez; Ima Moslemi; María de la O Rodriguez Martín; David Beltrán- Vaquero; María Paz Alonso-Reyero; Tomás Rodriguez-Bravo (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2016)
Objective: To assess the response and evolution of vaginal intraepithelial neoplasia (VAIN) after CO2 laser treatment.  Material and Methods: A retrospective study was conducted from a database of 139 women who had VAIN and were referred for treatment with CO2 laser. The lesions were detected following a hysterectomy. Human papillomavirus (HPV) typification was performed in all cases. The diagnosis of the lesions was performed by liquid based cytology and the location was by colposcopic study. Treatment with CO2 laser was performed in continuous mode. In the statistical study were assessed: age, diagnosis before hysterectomy, diagnosis before the laser treatment, the characteristics of the lesions and HPV genomic.  Results: 131 patients were evaluated after elimination of 8 cases of incomplete data. The age of patients ranged between 35 and 68 years. 68.70% were female aged 45 years and older. The cause of hysterectomy was myoma in 16.3% and the rest for other cervical pathology. 22 patients were diagnosed with VAIN II and 106 (80.91%) of VAIN III. The risk factors for recurrence were age over 45 years, type of VAIN and HPV 16 infection. The lesion with more recurrence was VAIN III, with 15.26%.  Conclusion: Laser vaporization can be considered a safe treatment for VAIN.